Keefektifan Penggunaan Google Classroom Dalam Pembelajaran Daring Selama Pandemi Covid-19 Pada Program Studi S1 Pendidikan Administrasi Perkantoran Universitas Negeri Surabaya - Ruri Nurul Aeni Wulandari; Lifa Farida Panduwinata (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2021)
The purpose of this study was to determine the effectiveness of using Google Classroom in online learning during the Covid-19 pandemic. The method used in this research is descriptive quantitative. The research sample was students of the Office Administration Education Study Program at the State University of Surabaya, batch 2017, 2018, and 2019, which means 95 people. The data was collected using a questionnaire, while the data analysis technique used a percentage. The results showed that Google Classroom was effectively applied in online learning during the Covid-19 pandemic.